1999
DOI: 10.1111/j.1540-8159.1999.tb00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Extraction of Problematic or Infected Permanent Pacemaker Leads: 1994–1996

Abstract: Of the 400,000-500,000 permanent pacemaker leads implanted worldwide each year, around 10% may eventually fail or become infected, becoming potential candidates for removal. Intravascular techniques for removing problematic or infected leads evolved over a 5-year period (1989-1993). This article analyzes results from January 1994 through April 1996, a period during which techniques were fairly stable. Extraction of 3,540 leads from 2,338 patients was attempted at 226 centers. Indications were: infection (27%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
202
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(217 citation statements)
references
References 22 publications
9
202
2
4
Order By: Relevance
“…Predictors of TLE difficulty have been evaluated in several prior single and multicenter studies. 5,[16][17][18] Many variables previously identified as predictors of TLE difficulty were confirmed in this study, including implant duration 3,5,[16][17][18] and the number of leads extracted. 13 In contrast to prior studies, both local and systemic infection were associated with more severe pocket scar and increased TLE difficulty.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Predictors of TLE difficulty have been evaluated in several prior single and multicenter studies. 5,[16][17][18] Many variables previously identified as predictors of TLE difficulty were confirmed in this study, including implant duration 3,5,[16][17][18] and the number of leads extracted. 13 In contrast to prior studies, both local and systemic infection were associated with more severe pocket scar and increased TLE difficulty.…”
Section: Discussionsupporting
confidence: 56%
“…13 In contrast to prior studies, both local and systemic infection were associated with more severe pocket scar and increased TLE difficulty. 5 The observed association between more severe pocket scar and infection is plausible given the pathologic changes that occur with infection including inflammation and granulation. Although this study was underpowered to detect relationship between major complications and pocket scar severity due to the small number of events, it is worth noting that the only major complication occurred in a patient with severe pocket severity and calcification within the pocket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 System extraction is associated with a small risk of major complications, particularly vascular lacerations causing haemothorax and death. 32,70,[79][80][81][82] Extraction-related mortality rates are 0.1-0.8 % in large experienced centres. 70,83 In one large, single-centre study, including more than 5,000 lead extractions, 43 % of which were due to infection, risk of major complications was 1.8 %, and minor complications 3.6 %.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…Byrd et al reported that the risk of failure or partial removal doubled for every 3 years of implant duration. 7 The Heart Rhythm Society expert consensus for transvenous lead extraction defines complete success of the procedure as the removal of all targeted leads and all lead material from the vascular space without occurrence of any permanently disabling complication or procedure-related death. Clinical success was defined as the removal of all targeted leads and lead material from the vascular space or retention of a small portion of the lead (<4 cm) when the residual part did not increase the risk of perforation, embolic events, or perpetuation of infection, in the absence of complications.…”
Section: Discussionmentioning
confidence: 99%